2015
DOI: 10.1111/phor.12115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Methods for 3D Reconstruction of Natural Surfaces from Parallel‐Axes UAV Images

Abstract: Recent advances in structure from motion (SfM) and dense matching algorithms enable surface reconstruction from unmanned aerial vehicle (UAV) images with high spatial resolution, allowing for new insights into earth surface processes. However, accuracy issues are inherent in parallel-axes UAV image configurations. In this study, the quality of digital elevation models (DEMs) is assessed using images from a simulated UAV flight. Five different SfM tools and three different cameras are compared. If ground contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 43 publications
2
144
0
3
Order By: Relevance
“…However, recent studies have revealed the presence of systematic errors in the automatic SfM workflow (Eltner and Schneider, 2015;Harwin et al, 2015;James and Robson, 2014;Sieberth et al, 2014). These errors have been found to originate from various sources such as low overlap, blurry images, flight configuration, number and distribution of GCPs, as well as the various geometric camera models used in the different SfM software.…”
Section: Suitability Of Uavs For Monitoring Purposesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent studies have revealed the presence of systematic errors in the automatic SfM workflow (Eltner and Schneider, 2015;Harwin et al, 2015;James and Robson, 2014;Sieberth et al, 2014). These errors have been found to originate from various sources such as low overlap, blurry images, flight configuration, number and distribution of GCPs, as well as the various geometric camera models used in the different SfM software.…”
Section: Suitability Of Uavs For Monitoring Purposesmentioning
confidence: 99%
“…This was found to be particularly relevant in the case of low-cost cameras and in the absence of GCPs. The unresolved distortion might form bowlshape systematic patterns that were recognisable either in the undistorted images (Eltner and Schneider, 2015) or in the vertical error distributions at ICPs (James and Robson, 2014).…”
Section: Suitability Of Uavs For Monitoring Purposesmentioning
confidence: 99%
See 2 more Smart Citations
“…This task is often referred to as registration, and is conventionally dependent on establishing ground control points (GCPs) which are fixed by a higher-order control method (usually Global Navigation Satellite System-GNSS or Global Positioning System). A number of studies have examined the effect of GCP networks (number and distribution) in UAS surveys, showing that significant errors are expected in SfM-based products where GCPs are not adopted [39,40]. Nevertheless, systematic DEM error can Remote Sens.…”
Section: Preflight Planningmentioning
confidence: 99%